Parasitic limb excision in a neonate: a rare occurrence - Murad Habib; Muhammad Amjad Chaudhary (SpringerOpen, 2022)
Abstract Background Parasitic limb is a rare congenital anomaly. Its incidence is less than 1 in 1 million live births. It refers to the type of conjoined twin in which tissues of an incompletely formed twin (parasite) are attached to and dependent upon a fully developed twin. Since it is a rare anomaly, all the cases should be reported. Case presentation This study reports a 3-day-old neonate admitted to the Children's Hospital Emergency. Her initial complaints were an extra limb arising from her lower back. She was born as a result of cousin marriage and was not diagnosed antenatally. The limb was attached to the lower lumbar region (L4, L5, S1). The limb was hypoplastic, and the baby was unable to hold it against the gravity but she cried when it was pinched suggesting pain sensations. Preoperative diagnostic workup was done, and parasitic limb was excised. Conclusion Every child with parasitic limb is a surgical dilemma. Thus, a multi-disciplinary approach and a carefully planned surgery with meticulous dissection can result in complete excision of a parasitic limb without any complications.